1998
DOI: 10.1063/1.122780
|View full text |Cite
|
Sign up to set email alerts
|

Improved carrier collection in intermixed InGaAs/GaAs quantum wells

Abstract: We have used photoluminescence up conversion to study the carrier capture times into intermixed InGaAs/GaAs quantum wells. We have found that the capture into the intermixed wells is markedly faster than capture into the reference ͑unintermixed͒ quantum wells. The reasons for the significant reduction in the capture time is related to the shape of the intermixed quantum well. Such a reduction in the capture time is beneficial both in terms of the quantum efficiency and the frequency response of intermixed opto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…4. The sign of Π C is consistent with majority spin injection as is typically observed for spin-LED containing Fe/AlGaAs or Fe/Al 2 O 3 tunnel injectors [5,9]. Since the Fe layer is incorporated outside of the resonant cavity, a parasitic polarization arising from magnetic circular dichroism (MCD) is absent in our device as longitudinal and transverse optical confinement are ensured by the DBR mirrors and airpost geometry, respectively, such that the emission never passes through the magnetic layer.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…4. The sign of Π C is consistent with majority spin injection as is typically observed for spin-LED containing Fe/AlGaAs or Fe/Al 2 O 3 tunnel injectors [5,9]. Since the Fe layer is incorporated outside of the resonant cavity, a parasitic polarization arising from magnetic circular dichroism (MCD) is absent in our device as longitudinal and transverse optical confinement are ensured by the DBR mirrors and airpost geometry, respectively, such that the emission never passes through the magnetic layer.…”
Section: Resultssupporting
confidence: 75%
“…Above threshold the carrier lifetime is on the order of a few tens of picoseconds and is limited primarily by the QW carrier capture time, which includes both diffusion in the barrier and capture by the well. Techniques such as QW intermixing [9] and impurity-mediated resonant tunnelling [10] have been shown experimentally to reduce the carrier capture time in InGaAs/GaAs QWs from 45 ps to 20 ps at 12 K and from 80-150 ps to 600 fs over the temperature range 10-150 K, respectively. Application of such techniques to the design of spin-VCSELs could result in larger values of Π C for a given, yet small, spin polarization.…”
Section: Resultsmentioning
confidence: 98%
“…The trapping time is commonly determined from the rise time of the PL signal for the basic transition in the QW. In the simplest case, e.g., in [5], the trapping time of charge carriers in a QW is determined in terms of the rise time of the PL signal for the basic transition in the QW; thus, this is done without separation of the trap ping time proper and the cooling time of charge carri ers in the QW. To determine the trapping time of charge carriers, Blom et al [6] measured the lumines cence rise times for the basic transition in a QW at excitation photon energies higher and lower than the band gap of the QW's barriers.…”
Section: Resultsmentioning
confidence: 99%
“…Femto second spectroscopy has become one of the basic methods for studying the ultrafast processes associated with various mechanisms of scattering and the subse quent recombination of charge carriers. This method provides a means for comprehensively examining the physical processes that control charge carrier dynam ics at all stages, from photoexcitation, followed by time evolution of charge carrier states, to the transition to equilibrium distribution [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…QWI has already been shown to be a useful and efficient method in several devices, including laser diodes, quantum well infrared photodetectors (QWIPs) and optical waveguides [1][2][3]. We have recently shown that carrier capture into intermixed InGaAs/GaAs quantum wells is markedly faster than capture into similar but nonintermixed quantum wells [4]. We argued that this improved carrier collection is due to the fact that intermixed quantum wells are wider at the top of the well and contain extensive concentration gradients along the growth direction.…”
mentioning
confidence: 99%